OSMANLININ ÜÇÜNCÜ POPÜLER BİLİM DERGİSİ MİR’ÂT - Yurtoğlu, Bilal (Nobel Akademik Yayıncılık, 2022)
The third scientific-philosophical journal in the Ottomans was Mir'at, which was started to be published in February 1863 (Ramadan 1279). Mir'at is the first illustrated magazine published in the Ottomans. The publisher of Mir'at is Refik Bey, one of the young people around Namık Kemal. The illustrations in the magazine are related to the Ottoman General Exhibition opened in 1863 and some of the agricultural machinery exhibited here. It is reported that these agricultural machines were produced and sent to the exhibition by the British Ransome & Sims Company. The pictures in the magazine were printed by French lithographer Mandouce, who lives in Istanbul. The journal contains scientific articles and figures explaining how the lunar and solar eclipses happen due to the lunar eclipse that will take place in Istanbul on June 3, 1863, with the mechanism of steam engines. It is stated that the writings and figures related to astronomy were controlled by Osman Sâib Efendi, the chief astrologer of the period. One of the important articles in the magazine is the translation article that Namık Kemal started to make from Montesquieu. In another important article written for the exhibition, it is explained which economic rules societies can prosper by following. Mir'at had to end its publication after its third issue, at the end of a polemic with Münif Efendi, who can be called the editor of Mecmua-i Fünûn.

Osmanlılarda Haziran 1862 (Muharrem 1279) tarihli Mecmua-i Fünûn, Aralık 1862 (Receb 1279) tarihli Mecmua-i İber-i İntibâh ya da sekizinci sayıdan sonraki adıyla Mecmua-i İbretnüma’nın ardından Şubat 1863’da (Ramazan 1279) yayınına başlanan üçüncü bilimsel-felsefî dergi Mir’ât’tır. Osmanlılarda çıkarılan ilk resimli dergi olarak bilinen Mir’ât’ın yayımcısı Namık Kemal’in çevresindeki gençlerden biri olan Refîk Bey’dir. İstanbul’da yaşayan litograf Mandouce tarafından basıldığı bildirilen dergideki resimlerin büyük çoğunluğu, 1863’te açılan Osmanlı Genel Sergisi (Sergî-i Umûmî-i Osmânî) ve burada teşhir edilen bazı tarım makinalarına ilişkindir. Bazılarının kullanımı açıklanan bu tarım araçları İngiliz Ransome & Sims Şirketi tarafından üretilip sergiye gönderilmiştir. Dergide, buhar makinalarının mekanizmasıyla 3 Haziran 1863’te İstanbul’da gerçekleşecek Ay tutulması dolayısıyla, Ay ve Güneş tutulmalarının nasıl oluştuğunun anlatıldığı, dönemin müneccimbaşısı Osman Sâib Efendi tarafından kontrol edilmiştir denilen, bilimsel yazılar ve şekiller de bulunmaktadır. Namık Kemal’in Montesquieu’dan yapmaya başladığı tercüme-tefrika ile sergi dolayısıyla ekonomik zenginlik elde etmeyi amaçlayan bir toplum ve devletin hangi kurallara dikkat etmesi gerektiğini anlatan tefrika-yazı, Mecmua-i Fünûn editörü denilebilecek Münif Efendi ile girdiği polemik sonucu kapanan derginin diğer önemli makaleleridir.
Keywords: Mir; Refik Bey; Münif Efendi; Mecmûai Fünûn; Ottoman General Exhibition; Namık Kemal; Montesquieu; Osman Sâib Efendi; Nicolas Mandouce; Ransome & Sims Company; Mir’ât; Refîk Bey; Münif Efendi; Mecmûai Fünûn; Sergî-i Umûmî-i Osmânî; Namık Kemâl; Montesquieu; Osman Sâib Efendi; Nicolas Mandouce